MOLECULAR AND CELLULAR MECHANISMS OF NEUROIMMUNE INTERACTIONS - Ibrokhimova Poshshokhon Saidahmadovna (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
This article explores the molecular and cellular foundations of the bidirectional communication between the nervous and immune systems. The roles of neurotransmitters cytokines and neuropeptides in neuroimmune signaling are analyzed. The research highlights the immune functions of microglia cells in the central nervous system and their importance in maintaining homeostasis. The role of neuroimmune disruptions in the development of pathological conditions is scientifically substantiated.